Sosialisasi dan Pendampingan Pembenahan Instalasi Kelistrikan Panti Asuhan Sultan Fatah Ngaliyan Semarang - Muhammad Amiruddin; Imadudin Harjanto; Bambang Hadi Kunaryo; Margono Margono; Nur Aksin (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The need for electricity for human life is increasing day by day, both for daily living needs and industrial needs. In reality, electricity doesn't always work as expected, sometimes it goes out and disrupts activities, although not often, that's why it's necessary to have backup electricity, especially for those used by many people. The aim of this program is to provide understanding to all administrators and students of related orphanages about the safety of electrical installations and knowledge about generators as backup electrical power sources as well as assistance in installing and improving electrical installations for generators. Socialization activities and assistance in improving the electrical installations of orphanages have run smoothly and met work targets, as evidenced by the increase in knowledge and understanding of related orphanage administrators and students regarding how to work, installing generators and the safety of electrical installations, especially regarding the type and size of cables that must be used. In this activity, the management and students accompanied by the service team succeeded in installing and testing the electrical installation for the generator. The results of testing the generator with a household load measured a voltage of 220 Volts, a current of 0.37 Ampere and a frequency of 50 Hz during daytime testing (minimal electrical load usage). Selection and use of NYY 2.5 mm2 cable which has a KHA (Current Carrying Strength) of 27 Amperes to support the maximum load of the orphanage which is measured at 7.18 Amperes.